2013
DOI: 10.1371/journal.pone.0061374
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Tick-Borne Encephalitis Virus in Baltic Countries and Eastern Poland

Abstract: Ticks were collected from the vegetation in the Baltic countries Estonia, Latvia, Lithuania and eastern Poland and analyzed for the presence of tick-borne encephalitis virus (TBEV) by amplification of the partial E and NS3 genes. In Estonia we found statistically significant differences in the TBEV prevalence between I. persulcatus and I. ricinus ticks (4.23% and 0.42%, respectively). In Latvia, the difference in TBEV prevalence between the two species was not statistically significant (1.02% for I. persulcatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 35 publications
3
71
0
4
Order By: Relevance
“…The presence and prevalence of other tick-borne pathogens (TBP) have previously been reported in questing ticks from the same regions of Estonia Geller et al, 2013;Katargina et al, 2013). The most frequently detected tick-borne pathogens were Borrelia burgdorferi s.l.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The presence and prevalence of other tick-borne pathogens (TBP) have previously been reported in questing ticks from the same regions of Estonia Geller et al, 2013;Katargina et al, 2013). The most frequently detected tick-borne pathogens were Borrelia burgdorferi s.l.…”
Section: Discussionmentioning
confidence: 86%
“…It may be suggested that Eastern Estonia is the most western limit of Candidatus R. tarasevichiae range, which corresponds with the western border of the geographical range of I. persulcatus, Thus, it will be interesting to investigate if this Rickettsia species may infect the sympatric tick species I. ricinus, as has been found for other tick-borne pathogens, such as the Asian lineage of B. myamotoi, and the Siberian subtype of TBEV Katargina et al, 2013). Although Candidatus R. tarasevichiae circulates in such a wide territory, from Estonia to Japan, it demonstrates a high rate of sequence homology between sequences of the partial citrate synthase gltA and ompA genes from different regions.…”
Section: Discussionmentioning
confidence: 99%
“…EEV ið gy ven ti rei ka lin gi du skir tin gi ðei mi nin kai -er kës ir stubu ri niai gy vû nai. Uþ si krë tu sios er kës per duo da vi ru sà svei koms er këms ir stu bu ri niams gy vû nams, ku rie rei kalin gi uþ krës ti EEV svei kas er kes jø mai ti ni mo si me tu [7]. San trau ka.…”
Section: Epidemiologijaunclassified
“…Dau giau nei 300 skir tin gø gy vû nø rû ðiø ga li bû ti EEV ne ðio to jais, áskai tant lau ki nius ir na mi nius þin duo lius, paukð èius ir rop lius [7]. Pa grin di niai EEV ðei mi nin kai yra grau þi kai.…”
unclassified
“…4). All 3 TBEV subtypes can co-circulate in areas where both tick species overlap [45][46][47]. Phylogenetic studies have shown that TBEV-Fe and TBEV-Sib are more closely related to each other than to TBEV-Eu, and that TBEV-Eu is more closely related to Louping ill virus, which is the only tickborne flavivirus in the United Kingdom.…”
Section: Subtype Distributionmentioning
confidence: 99%